1997
DOI: 10.1007/s002770050252
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous splenic rupture in two patients with a blastoid variant of mantle cell lymphoma

Abstract: Spontaneous rupture of the spleen is a rare complication of hematological malignancies, occurring most commonly in patients with acute leukemia, but it has been documented in chronic leukemias and also in lymphomas. We report two patients with histologically and immunohistochemically confirmed mantle cell lymphoma (MCL) who experienced a spontaneous splenic rupture. An 80-year-old woman and a 51-year-old man had a blastoid variant of MCL and responded poorly to conventional treatment. Both patients recovered a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 9 publications
0
19
0
1
Order By: Relevance
“…Pathological rupture of the spleen is most commonly seen in the hematological malignancies [31] , in which fragmentation and dissolution of the fibrous capsule of the spleen occur by infiltrating atypical lymphocytes, as seen in lymphoma or leukemia [20] . Giagounidis et al [32] have reported that male sex, adulthood, severe splenomegaly and cytoreductive chemotherapy are factors that are associated more often with rupture of the spleen in hematological malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological rupture of the spleen is most commonly seen in the hematological malignancies [31] , in which fragmentation and dissolution of the fibrous capsule of the spleen occur by infiltrating atypical lymphocytes, as seen in lymphoma or leukemia [20] . Giagounidis et al [32] have reported that male sex, adulthood, severe splenomegaly and cytoreductive chemotherapy are factors that are associated more often with rupture of the spleen in hematological malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Although MCL typically shows indolent histological features with a low proliferation rate, it is known to have a poorer prognosis than the other small cell lymphomas with a median survival of only 3-4 years. A blastoid variant of MCL shows large nuclei, a high proliferation activity, and an aggressive course [1,13,23,25,36,37]. Typically, MCL is presented in middle-aged or elderly patients [31] who have at diagnosis an advanced disease with generalized lymphadenopathy and often extranodal manifestations such as infiltrations of bone marrow, gastrointestinal tract, spleen, or Waldeyer's ring [1,3,5,6,10,22,24,26,28,35,36,38,39].…”
Section: Introductionmentioning
confidence: 99%
“…It should be considered that undetected structural abnormalities within the spleen may cause nontraumatic splenic rupture. Pathological rupture of the spleen is most commonly seen in the hematological malignancies [20], in which fragmentation and dissolution of the fibrous capsule of the spleen occur by infiltrating atypical lymphocytes, as seen in lymphoma or leukemia [21]. The most common symptom is left upper-quadrant abdominal pain.…”
Section: Discussionmentioning
confidence: 99%